COMPARATIVE EFFECT OF TWO STORAGE METHODS ON QUALITY OF OKRA (Abelmoschus esculentus l. Moench) FRUITS IN AWKA-SOUTH LOCAL GOVERNMENT AREA, NIGERIA - Iwuagwu, Christian Chukwunenye; Ezeufoh, U. V. (FUDMA JOURNAL OF SCIENCES, 2024)
An investigation was carried out at the research Laboratory of Plant Protection of Crop Science and Horticulture, Nnamdi Azikiwe University, Awka to compare effects of storage materials on quality of okra fruits (Abelmoschus esculentus L. Moench). The experimental design was a Completely Randomized Design (CRD) replicated six times. The experiment consisted of storing of freshly harvested okra fruits in two storage containers viz: woven baskets (lined with bitter leaves and unlined baskets) and perforated Paper Cartons (lined with bitter leaves and unlinedwith cartons). The baskets and perforated cartons containing the okra fruits were then kept on laboratory benches. Okra fruits in the storage containers were covered with white transparent nylon material and observed for 14 days. At the end of the period, the fruits were sorted out into relatively healthy fruits, rotted fruits, green fruits, light green fruits, spotted fruits and shriveled fruits. The weight loss of okra fruits was recorded to an accuracy of 0.01 g using mettle balance model (P1200). Results showed that packaging materials had significant effect on physical qualities of okra fruits after two weeks of storage, where unlined cartons had the highest (38.3%) number of relatively healthy fruits followed by 37.5 % in unlined baskets while the least (30.8%) was obtained in lined baskets. The results also showed that packaging materials had significant effect on moisture content of okra fruits stored in different storage materials where there was lesser moisture loss in okra fruits stored in lined cartons compared to other storage packages...